An Immunogram for an Individualized Assessment of the Antitumor Immune Response in Patients With Hepatocellular Carcinoma - Hu, Ying; Sun, Huaibo; Zhang, Henghui; Wang, Xianbo (Frontiers in Oncology, 2020)
In clinical practice, the cancer-immunity cycle of an individual patient with hepatocellular carcinoma (HCC) must be described to support the clinical management of cancer. The present study explored the immunograms of patients with liver cancer based on liver RNA sequencing data to visually display the individualized cancer-immunity cycles. Two independent HCC cohorts [The Cancer Genome Atlas (TCGA) and Liver Cancer-RIKEN, Japan (LIRI-JP) HCC cohorts] with whole exome sequencing (WES) data, RNA sequencing data, and clinical data from TCGA and International Cancer Genome Consortium (ICGC) were enrolled in this study. This study constructed HCC immunograms of cancer immune cells to visually explore the anticancer immune responses of patients with HCC. The patterns of the HCC immunograms were categorized into two clusters: hot and cold HCC immunograms. Favorable overall survival (OS) and disease-free survival (DFS) were observed in the hot immunogram cluster in the TCGA cohort. The results for LIRI-JP cohort were similar to the TCGA cohort. The OS of patients with HCC presenting the hot immunogram was longer than patients with the cold immunogram in the LIRI-JP HCC cohort. Compared with cold immunograms, hot immunograms were characterized by higher levels of immune cell infiltration and stronger immune signatures, including cytolytic activity, IFN-γ signature, immunocostimulator, immunoinhibitor, chemokine, adhesion molecule, MHC I, MHC II, and non-class MHC levels. The main difference in molecular features between hot and cold immunograms was reflected in WNT-CTNNB1 alterations and copy number variant (CNV) and loss of heterozygosity (LOH) scores, which are the molecular features associated with resistance to immunotherapy and tumor escape. The immunogram patterns were distinct in terms of the different molecular features of HCC tumors. The HCC immunogram for the cancer-immune cycle was able to visualize the personalized antitumor immune response of patients with HCC, and the patterns of the HCC immunograms contributed to the clinical outcomes of patients, which may facilitate an individualized assessment of the antitumor immune response for optimal personalized immunotherapy.